2021
DOI: 10.1182/hematology.2021000231
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of older adult or frail patients with multiple myeloma

Abstract: Older adults with multiple myeloma (MM) are a growing population, and personalizing treatment based on disease and health status is imperative. Similar to MM staging systems that provide disease-related prognostic information, myeloma-specific frailty tools can better identify subgroups at greatest risk for treatment-related toxicity and early treatment discontinuation, as well as predict overall survival. Several myeloma-specific validated tools are well studied. Although these fitness/frailty scores have sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Parameters predicting poor outcomes are well established, including cytogenetic abnormalities (CAs) such as t(4;14), t(14;16), t(14;20), ≥ 3 copies of chromosome band 1q21 (1q21 +), deletion of chromosome arm 1p (del(1p)), and deletion of chromosome band 17p13 (del(17p)) (Table 1 ); clinical biomarkers and features such as ISS stage 3 [ 3 ], high serum lactate dehydrogenase (LDH) [ 4 ], the presence of circulating plasma cells including plasma cell leukemia (PCL) [ 5 ], central nervous system (CNS) involvement [ 6 ], and plasmablastic morphology [ 7 ]; and host factors such as age, renal dysfunction, and frailty [ 8 ]. Other molecular parameters can also predict outcomes (Table 1 ), such as gene expression profiling (GEP) signatures, including the GEP70-gene signature from University of Arkansas for Medical Sciences (UAMS) [ 9 ] and the EMC-92 signature from the HOVON group [ 10 ]; a gene mutational status such as APOBEC (apolipoprotein B mRNA-editing enzyme, catalytic polypeptide)-type mutational signatures [ 11 ]; a high total number of mutations [ 12 ]; the presence of homologous recombination deficiency [ 13 ]; and the presence of chromothripsis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parameters predicting poor outcomes are well established, including cytogenetic abnormalities (CAs) such as t(4;14), t(14;16), t(14;20), ≥ 3 copies of chromosome band 1q21 (1q21 +), deletion of chromosome arm 1p (del(1p)), and deletion of chromosome band 17p13 (del(17p)) (Table 1 ); clinical biomarkers and features such as ISS stage 3 [ 3 ], high serum lactate dehydrogenase (LDH) [ 4 ], the presence of circulating plasma cells including plasma cell leukemia (PCL) [ 5 ], central nervous system (CNS) involvement [ 6 ], and plasmablastic morphology [ 7 ]; and host factors such as age, renal dysfunction, and frailty [ 8 ]. Other molecular parameters can also predict outcomes (Table 1 ), such as gene expression profiling (GEP) signatures, including the GEP70-gene signature from University of Arkansas for Medical Sciences (UAMS) [ 9 ] and the EMC-92 signature from the HOVON group [ 10 ]; a gene mutational status such as APOBEC (apolipoprotein B mRNA-editing enzyme, catalytic polypeptide)-type mutational signatures [ 11 ]; a high total number of mutations [ 12 ]; the presence of homologous recombination deficiency [ 13 ]; and the presence of chromothripsis [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal intensity of treatment in adults who are frail with multiple myeloma (MM) is often uncertain, given the higher risk of harm in patients who are frail on standard, intensive regimens. 1 , 2 Randomized controlled trials (RCTs) directly or indirectly exclude patients who are frail, limiting the generalizability of results to a large portion of patients treated in practice. 3 , 4 Although analyses from RCTs and observational studies consistently show that frailty is associated with higher risks of treatment toxicity, treatment discontinuation, and mortality, 5 this evidence does little to inform the key clinical question, that is, whether to administer to patients who are frail, in practice, the same intensity of treatments evaluated in the younger, fitter patients in RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…Although many pivotal ASCT randomized controlled trials (RCT) excluded older adults (3,4), several large retrospective studies and a meta-analysis have shown that ASCT is safe and feasible in selected older adults as per their local or study criteria (5,6). There are a wide variety of tools that may be used to evaluate a patient for ASCT including performance status, geriatric assessment tools and frailty indices (7,8); however, there a lack of agreement between these tools (9) and subsequently wide variation in their usage. Furthermore, there is wide heterogeneity in the eligibility of ASCT in older adults across different institutions and regions.…”
Section: Introductionmentioning
confidence: 99%